The Knowledge, Attitude and Practices Regarding HBV Infection of Married Women in the Reproductive Age Group living in Different Districts of Bangladesh - Rahman, Md Atiqur; Mannan, Sultana Rokeya (Medicine Today, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The present study was conducted to know the knowledge, attitude and practices of 300 married women in the reproductive age group living in different districts of Bangladesh, regarding HBV infection. Only 20% of the women were found aware of the mode of transmission of HBV. However, 50% of the women were having the misconceptions regarding mode of transmission of HBV. 4% of women, 30% of children up to 5 years and 15% of children above 5 years were fully immunized with hepatitis B vaccine. 80% of children up to 5 years and 75% of children above 5 years were fully immunized as per universal immunization programme. Hence, the results of the study clearly indicated the low immunization rate with vaccine against HBV under universal immunization programme and this further potentiated the need to grow public awareness about vaccination against Hepatitis B by focusing the beneficial effect of early immunization through public electronic media. Key words: KAP; HBV; Immunization; Perinatal transmission DOI: 10.3329/medtoday.v22i1.5602 Medicine Today Vol.22(1) 2010. 29-31